Leadership and the one minute manager increasing effectiveness through situational leadership - Blanchard, Kenneth H.; Zigarmi, Patricia; Zigarmi, Drea. (New York William Morrow, 1985)
Providing a guide to effective business leadership, three management consultants' important concepts and techniques of leadership, including flexibility, diagnosis, contracts, building skill, confidence, and autonomy in others.

In clear, simple terms Leadership and the One Minute Manager teaches managers the art of Situational Leadership--a simple system that refutes the conventional management mandate of treating all employees equally. Here, you'll learn why tailoring management styles to individual employees is so important why knowing when to delegate, support, or direct is critical how to identify the leadership style suited to a particular person and how consistent use of the One Minute techniques will produce better management and enhanced motivation on all levels. This remarkable, easy-to-follow book is a priceless guide to creative, personalized leadership that elicits the best performance from your staff--and the best bottom line for any business. If your management motto is "everyone should be treated equally," Leadership and the One Minute Manager will show you why this style not only hinders workplace efficiency, but also frustrates your staff. In clear, simple terms, Ken Blanchard, co-author of the enormously popular The One Minute Manager., coupled with business gurus Patricia and Drea Zigarmi, teach managers the art of Situational Leadership.. You'll learn why tailoring management styles to individual employees is so important when to delegate, support, or direct how to identify the leadership style suited to a particular person and how consistent use of the One Minute techniques will produce better management and enhanced motivation on all levels. This remarkable, easy-to-follow book is a priceless guide to creative, personalized leadership that elicits the best performance from your staff and the best bottom line for any business. -- Book jacket.
A Visit from an Entrepreneur -- Being Successful -- Thinking Differently About Leadership -- Different Strokes for Different Folks -- Leadership Style: Perceptions of Others -- Leadership Style Flexibility -- The Four Basic Leadership Styles -- No Best Leadership Style -- Think Before You Act -- Flexibility: A Review -- The Four Basic Leadership Styles: A Summary -- Diagnosing Development Level -- Matching Leadership Style to Development Level -- Situational Leadership and One Minute Management -- Different Strokes for the Same Folks -- Developing Competence and Commitment -- Turning Around Performance Problems -- One Minute Management and Situational Leadership: A Review -- Sharing What You're Doing -- Contracting for Leadership Style -- Positive Assumptions About People -- Becoming a Situational Leader -- Praisings.
Keywords: Leadership; Management